Antenatal screening in the UK. Issue 11 (November 2021) - Moore, Judith; Fatouta, Rawia
Abstract: The process of screening aims to reduce the burden of disease. In pregnancy this is relevant to both the mother and her baby. There are national screening programmes for infectious disease, haemoglobinopathy and fetal anomalies, all of which have the potential to reduce the life-long burden of disease in the newborn. But screening extends beyond these programmes and when risk factors are identified, interventions might be instigated to reduce the impact of disease on pregnancy outcomes. This article reviews screening in its broadest sense. It describes the various screening opportunities and considers the actions that can be taken to optimize the health of the mother and her baby. The process of screening continues throughout pregnancy, just as risks evolve as pregnancy progresses.